RESPON PETANI TERHADAP PELAKSANAAN DISPLAI PADI GOGO VUB PADA LAHAN SUB OPTIMAL DI SULAWESI SELATAN - Sunanto Sunanto; Abd Wahid Rauf (Hasanuddin University, 2018)
RESPON PETANI TERHADAP PELAKSANAAN DISPLAI PADI GOGO VUB PADA LAHAN SUB OPTIMAL DI SULAWESI SELATAN Farmers Response on VUB “Gogo” Rice Display on Sub-Optimal Landin South Sulawesi Sunanto * dan Abd. Wahid Rauf Balai Pengkajian Teknologi Pertanian (BPTP) Sulawesi Selatan *Kontak penulis: sunanto_bptpsulsel@yahoo.co.id The Gogo rice is a food crop that contributes to food self-sufficiency. Food demand, especially rice continues to increase along with population growth. Because of the higher food needs and the narrowness of fertile land, due to the land conversion function. So the utilization of sub-optimal lands / landed with appropriate food crops. The potency of thesub-optimal area in South Sulawesi is 274,549 hectares. The purpose of this research is to know how sub-optimal land used and farmer appraisal to gogo rice. This research was conducted in Wajo and Jeneponto Regencies from January to December 2017. The research used survey method and display of gogo rice plant NSV of Agricultural Research Agency in the field. The number of farmers taken as a sample of 80 farmers.The technique of collecting data by interview method and observation of vegetative and generations of display gogo rice plant. The collected data are then tabulated and then analyzed descriptively and test the agreement and business feasibility. The activities of rice farming on sub-optimal land are done by farmers that have the productive age. Theapplication of rice farming technology to suboptimal land has not been intensive yet. Display gogo rice plant VUB resulted from Agricultural Research Agency appropriate to be planted with / out sub-optimal land of dry land and irrigated rice fields limited. Understanding farmers on superior gogo rice are not optimal (77.50%). Farmer's preference to superior gogo farmers. Rice farming of farmers provides income(implicative). Rp 4.575.000/ha, (explicit). Rp 7.245.000/ha and R/C (implicative ) 1.62 and (explicit ) 2.53.Keywords: upland rice; VUB; land; sub optimal.